THE INFLUENCE OF CERTIFIED TEACHERS ON EDUCATORS GRADUATES OF STATE HIGH SCHOOL SOCIAL SCIENCES MAJORS IN JAMBI CITY: PANEL DATA APPROACH - Fitri, Ani; Sari, Vitri Purnama (Magister Program Studi Pendidikan Ekonomi, 2026)
The quality of educational output is a crucial indicator of successful human resource development, but the effectiveness of teacher certification policies in improving student academic achievement remains a matter of debate in the educational management literature. This study aims to empirically analyze the influence of certified teachers on the graduation rate of social studies students at public high schools in Jambi City. Using a quantitative approach, this study analyzed panel data covering 11 schools during the 2017–2019 period. The selected estimation method through formal testing is the Fixed Effect Model (FEM). The results revealed that the presence of certified teachers has a positive and significant effect on student graduation rates (p = 0.0099 < 0.05), with a regression coefficient of 1.518. The Adjusted R-squared value of 0.7209 indicates that teacher professionalism contributes dominantly to the variation in student academic achievement, amounting to 72.09%. The novelty of this study lies in the application of panel data analysis to evaluate the impact of education policies at the local level, which is able to capture specific characteristics between schools that are not observed in conventional cross-sectional studies. Theoretically, these findings strengthen Human Capital Theory by proving that standardizing teacher competencies through certification is a strategic investment that improves internal school efficiency. The implications of this research emphasize the importance for policymakers to improve the quality of post-certification training to ensure the sustainability of its positive impact on graduate quality. This study contributes to the literature on educational effectiveness in developing countries by empirically demonstrating the crucial role of teachers as the primary cognitive agents in the school system.